The Search for Wondla - Diterlizzi, Tony (New York Silmon and Schuster, 2011)
Living in isolation with a robot on what appears to be an alieworld populated with bizarre life forms, a twelve-year-old human girl called Eva Nine sets out on a journey to find others like her. Features "augmented reality" pages, in which readers with a webcam can access additional information about Eva Nine's world. Suggested level: intermediate, junior secondary.
Include Color Illustration
Keywords: Human-alien encounters -- Identity (Philosophical concept) -- Robots